2018
DOI: 10.1039/c7sc03672h
|View full text |Cite
|
Sign up to set email alerts
|

Impact electrochemistry reveals that graphene nanoplatelets catalyse the oxidation of dopamineviaadsorption

Abstract: Single entity measurements (‘nano-impacts’) reveal that adsorption of dopamine and its oxidised product on the graphene is the key factor causing the observed catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Single NP collision electrochemistry has attracted increasing interest over the past decades, motivated by the unique electrochemical behaviors of single NPs during their stochastic collision processes at an ultramicroelectrode (UME) surface, unveiling the intrinsic properties masked in ensemble‐averaged measurements . Stochastic collision electrochemical measurements have been widely applied in many applications ranging from electrocatalytic amplification and direct electrochemical stripping of individual metal NPs to soft particles and blocking detection of biologically relevant samples .…”
Section: Figuresupporting
confidence: 89%
“…Single NP collision electrochemistry has attracted increasing interest over the past decades, motivated by the unique electrochemical behaviors of single NPs during their stochastic collision processes at an ultramicroelectrode (UME) surface, unveiling the intrinsic properties masked in ensemble‐averaged measurements . Stochastic collision electrochemical measurements have been widely applied in many applications ranging from electrocatalytic amplification and direct electrochemical stripping of individual metal NPs to soft particles and blocking detection of biologically relevant samples .…”
Section: Figuresupporting
confidence: 89%
“…[32][33][34][35][36][37] Stochastic collision electrochemical measurements have been widely applied in many applications ranging from electrocatalytic amplification and direct electrochemical stripping of individual metal NPs to soft particles and blocking detection of biologically relevant samples. [32][33][34][35][36][37] Stochastic collision electrochemical measurements have been widely applied in many applications ranging from electrocatalytic amplification and direct electrochemical stripping of individual metal NPs to soft particles and blocking detection of biologically relevant samples.…”
mentioning
confidence: 99%
“…Single NP collision electrochemistry has attracted increasing interest over the past decades,m otivated by the unique electrochemical behaviors of single NPs during their stochastic collision processes at an ultramicroelectrode (UME) surface,u nveiling the intrinsic properties masked in ensemble-averaged measurements. [32][33][34][35][36][37] Stochastic collision electrochemical measurements have been widely applied in many applications ranging from electrocatalytic amplification and direct electrochemical stripping of individual metal NPs to soft particles and blocking detection of biologically relevant samples. [38,39] Recently,Comptonsgroup assessed the electrocatalytic activity of single NPs by stochastic collision measurements.…”
mentioning
confidence: 99%
“…The partial oxidation of dopamine suggested that the continuous electron transfer was blocked by the previous oxidative products, revealing the fact that the electrons were transferred on the surface of GNPs rather than passing through them (Figure d). The conclusion provided the support information for the better understanding of the oxidation of dopamine catalyzed by GNPs …”
Section: Development Of Nanoimpact Methodsmentioning
confidence: 70%
“…d) Illustration of the charge diffusion model. All panels reproduced under the terms of the Creative Commons Attribution 3.0 Unported Licence . Copyright 2018, The Royal Society of Chemistry.…”
Section: Development Of Nanoimpact Methodsmentioning
confidence: 99%